Identificação de padrões da dengue em municípios paulistas entre os anos de 2003 a 2011 - Oliveira, Érika Ramos de [UNESP] (2014)
This thesis aimed to identify patterns of Aedes (Stegomya) L. aegypti, vector of dengue disease in cities of São Paulo state between 2003-2011. The studied cities were Araçatuba, Bauru, Campinas, Marília, São José do Rio Preto, São Paulo, Santos, Sorocaba, Ribeirão Preto and Presidente Prudente in Brazil. The statistical technique of Cluster Analysis was used to classify these cities, where the variables related to dengue vector were chosen. The annual variables adopted were mean maximum temperature, mean minimum temperature, rainy days, average rainfall, population density, index of house infestation (IIP), resistance to temephos, rate of indigenous and imported dengue cases, as well as the altitude as fixed variable. The results showed that the patterns of dengue are dynamic throughout the studied period for the cities in focus. Cities were grouped into three more permanent groups, although there are changes in formation of these groups over studied time. The most consistent groups indicated a relation to the climatic classification of Köppen-Geiger, showing that the climate affects the dengue vector and its epidemiology. The city of Santos was classified as the only group in each year to present a distinct profile for bioecology and resistance to temephos in Ae. aegypti and dengue consecutively